A new set of mouse models to determine the role of the anti‐aging factor Klotho in late‐onset Alzheimer's disease. (1st February 2022) - Preuss, Christoph; Kotredes, Kevin P; Garceau, Dylan; Howell, Gareth R; Sasner, Michael; Carter, Gregory W
Abstract: Background: Apolipoprotein E4 (APOE4) is the single largest genetic risk factor for developing sporadic late‐onset Alzheimer's disease (LOAD). Despite this increased genetic risk profile, APOE4 carriers are not uniformly fated to develop LOAD in the course of their lifetime. Two common missense variants (p.F352V; p.C370S) in the aging factor Klotho have been shown to modify age of onset and reduce amyloid plaque deposition, specifically in APOE4 carriers. The combination of these two coding variants define the protective Klotho V/S (KL‐V/S) and the risk Klotho F/C (KL‐F/C) haplotypes. The protective KL‐V/S haplotype has been associated with a significant reduction in the lifetime risk of developing LOAD (OR=0.69) and lower amyloid burden in APOE4 but not APOE3 carriers. Method: Here, we used publicly available GWAS summary statistics to translate disease‐associated Klotho variants into novel mouse models of LOAD. We performed comparative sequence analysis between human and mouse to create a novel knock‐in strategy for modelling human klotho variants in an in‐vivo model. Result: Human Klotho shows 86% amino acid identity with the mouse protein but differs at a key amino acid position. While the LOAD associated variant at position F352 in klotho is remarkably conserved, the cysteine residue at position 370 is substituted by serine in mice creating a human‐specific haplotype. In order to model both human klotho haplotypes, we created two novel mouse models that express both the native KL‐F/C and protective KL‐V/S alleles. We will present validation data including transcriptomics and functional assays for the novel klotho mouse models. Conclusion: This is to our knowledge, the first instance of a "humanized" knock‐in strategy that targets LOAD‐associated variants in the important anti‐aging factor. Our strategy integrates human and mouse data, with the aim to define the role of klotho as a resilience factor in LOAD and validate its interaction with APOE4 in‐vivo.